Preliminary analysis: Background parenchymal 18F-FDG uptake in breast cancer patients appears to correlate with background parenchymal enhancement and to vary by distance from the index cancer. Issue 110 (January 2019) - Kim, Eric; Mema, Eralda; Axelrod, Deborah; Sigmund, Eric; Kim, Sungheon Gene; Babb, James; Melsaether, Amy N
Abstract: Purpose: To investigate how breast parenchymal uptake (BPU) of 18F-FDG on positron emission tomography/ magnetic resonance imaging (PET/MRI) in patients with breast cancer is related to background parenchymal enhancement (BPE), amount of fibroglandular tissue (FGT), and age, as well as whether BPU varies as a function of distance from the primary breast cancer. Materials and Methods: In this institutional review board (IRB)-approved retrospective study, 40 patients (all female, ages 32–80 years, mean 52 years) gave informed consent prior to undergoing contrast enhanced breast PET/MRI from 3/2015 to 2/2018. Of the 40 patients, 6 were excluded for multicentric or bilateral cancers, 1 for current lactation and 6 because the raw data from their scans were corrupted. The remaining 27 patients (all female, ages 33 to 80 years, mean age 53 years) comprised the study population. Prone PET and contrast-enhanced MR data were acquired simultaneously on a 3-T integrated PET/ MR system. BPU was measured as SUVmax of a 1.5 cm 3 volume of interest 1) in the same quadrant of the ipsilateral breast, 5 mm from the index lesion; 2) in the opposite quadrant of the ipsilateral breast; and 3) in contralateral breast, quadrant matched to the opposite quadrant of the ipsilateral breast. The maximum standardized uptake value (SUVmax) of the index cancer was measured using a VOI that included the entire volume of the index lesion. Bleed from the primary tumor was corrected for (PET edge, MIM). FGT and BPE was assessed by 2 readers on a 4-point scale in accordance with BI-RADS lexicon. The Wilcoxon signed rank test and the Spearman rank correlation test were performed. Results: BPU was significantly greater in the same quadrant as the breast cancer as compared with the opposite quadrant of the same breast (p < 0.001 for both readers) and was significantly greater in the opposite quadrant of the same breast compared to the matched quadrant of the contralateral breast (p = 0.002 for reader 1 and <0.001 for reader 2). While the FGT SUVmax in the same quadrant as the cancer correlated significantly with SUVmax of the index lesion, the FGT SUVmax in the opposite quadrant of the same breast and in the matched quadrant of the contralateral breast did not. The FGT SUVmax in the contralateral breast positively correlated with the degree of BPE and negatively correlated with age, but did not show a significant correlation with the amount of FGT for either reader. Conclusion: There appears to be an inverse correlation between metabolic activity of normal breast parenchyma and distance from the index cancer. BPU significantly correlates with BPE.